(untitled) (Revista Internacional de Formação de Professores, 2016)
Based on an array of evidence courses from university campus online training practices and teacher narratives findings has advanced our understanding of the power of electronic portfolios (eportfolios) research and practice and its potential to support faculty learning. This paper writes about a university scholar’ self-consciously value-centered metadiscourse to review e-portfolio knowledge goals and progress. The work meta-synthesised other teachers´ remembered thoughts, emotions and actions in order to recall shared focal themes (methodological and practical experiences) on e-portfolios that offer a new perspective on information behavior of people. The assumed scholar had used a first-person to establish the context (problems, methods and results) of e-portfolios for information and interaction, report findings, and raise issues within his narrative discourse about cultural aspects of university. Finally, the scholar as an applied ethnographer may have indicated about supposed relationships in the e-portfolio research literature between the construction of a ‘voice’ in university teachers’ ethnographic narratives and the university culture.